2015
DOI: 10.1167/iovs.15-16547
|View full text |Cite
|
Sign up to set email alerts
|

Normal Perceptual Sensitivity Arising From Weakly Reflective Cone Photoreceptors

Abstract: Low cone reflectance cannot be used as a reliable indicator of cone sensitivity to light in normal retinas. To improve assessment of early retinal pathology, other diagnostic criteria should be employed along with imaging and cone-based microperimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 50 publications
4
62
0
2
Order By: Relevance
“…In addition to their number and position, one of the most noticeable features of the photoreceptors is the spatial variability of their reflectance, which has been clearly detected with all AO imaging modalities [9][10][11][12][13][14][15][16][17][18]. From early observations, it has been shown that the cones change their reflectance with time even in healthy retinas [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their number and position, one of the most noticeable features of the photoreceptors is the spatial variability of their reflectance, which has been clearly detected with all AO imaging modalities [9][10][11][12][13][14][15][16][17][18]. From early observations, it has been shown that the cones change their reflectance with time even in healthy retinas [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the changes in reflectance occur independently between the cones [9] and that the cones change their brightness on time scales ranging from milliseconds [10,17] and seconds [11,15,16] to hours [9,12,13], days [14], months or years [18].…”
Section: Introductionmentioning
confidence: 99%
“…This background light set fundamental limits to experimental designs. For example, single cone sensitivity thresholds are necessarily reported as thresholds to light increments [6,15,17]. In a study of single cone color appearance, background light options were limited, requiring high intensity fields to mask the residual background of the stimulus light [16].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical applications, the higher dynamic range of stimulus lights will enable dark adapted vision-as well as rod function testing. Rod function testing is of importance for clinically oriented visual testing [15,31,32], especially with regard to retinal diseases affecting mesopic and scotopic vision, where early signs of the disease is most likely found in reduced rod function [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation